Necrosing complications and intercurrences in rhinomodeling with hyaluronic acid: integrative literature review - Beserra de Oliveira Menezes, Maria Eduarda (2023)
Objective: To describe the adverse effects, intercurrences and complications of filling with hyaluronic acid in the nose region, indicating possible causes for the problems presented after the procedure. Methodology: This is an integrative review carried out in the following databases: Medline via PubMed, SciELO and Lilacs, with articles included in the period 2013 to 2023, using the descriptors, Hyaluronic acid; Necrosis; Dermal fillers; Nose. The integrated search was performed by joining the descriptors with the Boolean operator “AND”. Nine publications were analyzed. Results: The selected works were identified, listing data related to title, author, year of publication, type of study, methodology, main intercurrences found and conclusion of the study. After analyzing the studies, it was observed thatthe occurrence of complications after the application of hyaluronic acid is not frequent. In order for the aggravation not to occur, it is necessary that the first signs and symptoms are analyzed in order to follow the most appropriateprotocol in order to prevent or reverse it. Conclusion: Following simple safety steps and having refined anatomical knowledge, fillers can be a good tool for a safe and comprehensive improvement of rhinomodelation.